A novel tri-layer nanoindentation method to measure the mechanical properties of a porous brittle ultra-low-k dielectric thin film. (May 2017) - Du, Yingjie; Xu, Tingge; Shaw, Thomas M.; Liu, Xiao Hu; Bonilla, Griselda; Li, Han; Lu, Hongbing
Abstract: The mechanical properties of two porous ultra-low-k (ULK) dielectric thin films (porous carbon-doped silicon dioxide (pSiCOH); and octamethylcyclotetrasiloxane (OMCTS)) were measured by nanoindentation. Since a direct contact of a nanoindentation tip with a thin and brittle ULK film will likely induce damage to the film and thus alters its mechanical response, the mechanical properties measured from direct nanoindentation on an ULK film do not necessarily represent the behavior of an ULK thin film in service condition. To circumvent this difficulty, a novel tri-layer configuration was used for sample preparation. In this method, a thin layer of tetraethyl orthosilicate (TEOS) silica was deposited on an ULK thin film to protect it from direct contact with a nanoindenter tip. A nanoindenter tip was in contact with TEOS coating on the layered film in nanoindentation, and the collected data was subsequently analyzed by finite element analysis. The Ogden hyperfoam model was used as the constitutive law for the ULK film in simulations, and found to be appropriate. Results indicate that the linear elastic model is only applicable for very small strains. At large strains the ULK films show nonlinear behavior due to densification of the porous ULK material under compaction. The moduli for the pSiCOH and OMCTS dielectric films were determined as 2.6 GPa and 5.2 GPa, respectively.